Hepatitis B vaccine antibody response and the risk of clinical AIDS or death. - Michael L Landrum (Public Library of Science (PLoS), 2012)
Background Whether seroresponse to a vaccine such as hepatitis B virus (HBV) vaccine can provide a measure of the functional immune status of HIV-infected persons is unknown.This study evaluated the relationship between HBV vaccine seroresponses and progression to clinical AIDS or death. Methods and findings From a large HIV cohort, we evaluated those who received HBV vaccine only after HIV diagnosis and had anti-HBs determination 1-12 months after the last vaccine dose. Non-response and positive response were defined as anti-HBs <10 and ≥ 10 IU/L, respectively. Participants were followed from date of last vaccination to clinical AIDS, death, or last visit. Univariate and multivariable risk of progression to clinical AIDS or death were evaluated with Cox regression models. A total of 795 participants vaccinated from 1986-2010 were included, of which 41% were responders. During 3,872 person-years of observation, 122 AIDS or death events occurred (53% after 1995). Twenty-two percent of non-responders experienced clinical AIDS or death compared with 5% of responders (p<0.001). Non-response to HBV vaccine was associated with a greater than 2-fold increased risk of clinical AIDS or death (HR 2.47; 95% CI, 1.38-4.43) compared with a positive response, after adjusting for CD4 count, HIV viral load, HAART use, and delayed type hypersensitivity skin test responses (an in vivo marker of cell-mediated immunity). This association remained evident among those with CD4 count ≥ 500 cells/mm³ (HR 3.40; 95% CI, 1.39-8.32). Conclusions HBV vaccine responses may have utility in assessing functional immune status and risk stratificating HIV-infected individuals, including those with CD4 count ≥ 500 cells/mm³.